A sucessão geracional na agricultura familiar num contexto de mercantilização e modernização: um estudo em duas comunidades do Sudoeste do Paraná - Kischener, Manoel Adir (2015)
The new pattern of modernization of agriculture and the commodification in force in most rural areas of Brazil is also present in the Southwest of Paraná. So, study the strategy of social reproduction of family farming and its generational succession may reflect the same factors that condition this new rurality. In this sense, looking ascertain what are the factors affecting the generational succession of the family farm and see how the modernization of agriculture to become more complex; to this end, we started with a comparative study between two communities, which required interviews with 50 rural families followed by focus group sessions. From this study, it was noted that the factors that favor the permanence of young people in rural areas are mainly income, community values and the inclusion of life projects of the children in the family social reproduction strategies.